2015
DOI: 10.4018/ijthi.2015040105
|View full text |Cite
|
Sign up to set email alerts
|

Designing and Evaluating Digital Game-Based Learning with the ARCS Motivation Model, Humor, and Animation

Abstract: Multimedia teaching applications have been widely utilized in various subjects. The presentation of teaching materials with animations and games helps to stimulate the visual sense and enhance the learning motivation of learners. Successful learning, however, requires the stimulation of learning motivation that can inspire learners to achieve the desired learning objectives. This study combines the ARCS (Attention, Relevance, Confidence, Satisfaction) motivation model, and humor to design a set of multimedia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…Professional growth would remarkably and positively affect job satisfaction. Lee and Hao (2015) indicated that training contents, teacher quality, and training effectiveness in continuing education showed significantly positive effects on satisfaction. Wang and Han (2015) pointed out the remarkably positive effects of training plan, environment equipment, and training effectiveness in continuing education on satisfaction with value commitment.…”
Section: H2mentioning
confidence: 99%
See 1 more Smart Citation
“…Professional growth would remarkably and positively affect job satisfaction. Lee and Hao (2015) indicated that training contents, teacher quality, and training effectiveness in continuing education showed significantly positive effects on satisfaction. Wang and Han (2015) pointed out the remarkably positive effects of training plan, environment equipment, and training effectiveness in continuing education on satisfaction with value commitment.…”
Section: H2mentioning
confidence: 99%
“…Referring to Lee and Hao (2015), the dimensions of administrative competence, professional competence, and professional ethics for librarians' professional growth are utilized in this study.…”
Section: Professional Growthmentioning
confidence: 99%
“…They concluded that using the ARCS model as the design framework did enhance learning motivation and increase learning performance. Lee and Hao (2015) combined the ARCS motivation model, and humor to design a set of multimedia applications to develop a Cat's Cradle Multimedia Learning System (CCMLS). Significance was also found in ARCS learning motivation and perceived fun of teaching materials.…”
Section: Arcs Modelmentioning
confidence: 99%
“…Game-designed education aimed to induce and foster students' creativity and allowed students applying imagination, with the experiences and knowledge in the game-based learning process, to induce "fluency", "openness", "flexibility", "uniqueness", and "elaboration" in cognition as well as cultivate "adventure", "curiosity", "imagination", and "challenge" in affection (MichelaMortara et al, 2014). Lee and Hao (2015) proposed that game-based teaching should design story situations and skills according to learning goals. Subasi, Alickovic, and Kevric (2017) mentioned that games were the method to induce learning motivation, but not the learning focus, that activities suitable for the practice at various stages and proper difficulties are designed with clearly rules, attractive situations, and understanding of learners' knowledge and skills.…”
Section: Digital Game-based Teachingmentioning
confidence: 99%